2021
DOI: 10.3390/cancers13051061
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Growth of Breast Cancer-Associated Brain Tumors by the Osteocyte-Derived Conditioned Medium

Abstract: The brain is a common site of metastasis from advanced breast cancer but few effective treatments are available. We examined a therapeutic option with a conditioned medium (CM), focusing on the role of Lrp5 and β-catenin in Wnt signaling, and IL1ra in osteocytes. Osteocytes presented the innate anti-tumor effect and the overexpression of the above genes strengthened their action. In a mouse model, the injection of their CM inhibited mammary tumors and tumor-driven osteolysis. Importantly, Lrp5- and/or IL1ra-ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 52 publications
(34 reference statements)
1
36
0
Order By: Relevance
“…One such multi-tasking protein is histone H4 that packs DNA in the nucleus and stimulates innate immune responses outside of the cell 49 . We previously reported that extracellular histone H4 served as a tumor suppressor 50 . Another moonlighting example is a high mobility group box 1 (HMGB1) protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One such multi-tasking protein is histone H4 that packs DNA in the nucleus and stimulates innate immune responses outside of the cell 49 . We previously reported that extracellular histone H4 served as a tumor suppressor 50 . Another moonlighting example is a high mobility group box 1 (HMGB1) protein.…”
Section: Discussionmentioning
confidence: 99%
“…In the generation of iTS cells from osteocytes, we have previously shown that the overexpression of β-catenin and Lrp5 but not Lrp6 promoted the anti-tumor capabilities and the protection of tumor-invased bone 1 . In osteocytes and MSCs, the overexpression of multiple pro-tumorigenic genes and the administration of tumor-promoting compounds have been shown to generate iTSC that significantly inhibited the progression of adjacent tumors 1 - 3 . Further analyses are needed to elucidate the requirement for creating effective iTS CM from varing tumor and non-tumor cells, considering types of target cancer cells, as well as pathways and genes to be activated and overexpressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these agents significantly improve the quality of life in patients with bone metastasis and the risk of bone fracture, their efficacy is in many cases insufficient to prevent tumor-induced bone loss and eliminate cancer cells from the bone. To examine the possibility of developing a novel treatment option, we herein examined a recent technology of induced tumor-suppressing cells (iTSCs) that was successfully applied to osteocytes, mesenchymal stem cells (MSCs), and tumor cells [ 10 , 11 , 12 , 13 ]. In the iTSC technology, a dichotomous role of oncogenic signaling in tumor promotion as well as in tumor suppression is utilized.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is well known that the activation of Wnt signaling in tumor cells by the overexpression of β-catenin or Lrp5, or the application of a pharmacological Wnt activator, promotes tumor progression [ 13 ]. However, our previous studies have shown that Wnt-activated osteocytes, MSCs, and tumor cells produce tumor-suppressing secretomes, and their conditioned medium (CM) serves as a potent tumor-suppressing agent [ 10 , 11 , 13 ]. The question herein is whether it is possible to convert osteoclasts into iTSCs and generate bone-protective, tumor-suppressing secretomes by activating oncogenic signaling.…”
Section: Introductionmentioning
confidence: 99%